Nine Mitochondrial Genomes of the Pyraloidea and Their Phylogenetic Implications (Lepidoptera) - Xiaomeng Liu (MDPI AG, 2021)
The Pyraloidea is one of the species-rich superfamilies of Lepidoptera and contains numerous economically important pest species that cause great loss in crop production. Here, we sequenced and annotated nine complete mitogenomes for Pyraloidea, and further performed various phylogenetic analyses, to improve our understanding of mitogenomic evolution and phylogeny of this superfamily. The nine mitogenomes were circular, double-stranded molecules, with the lengths ranging from 15,214 bp to 15,422 bp, which are comparable to other reported pyraloid mitogenomes in size. Gene content and arrangement were highly conserved and are typical of Lepidoptera. Based on the hitherto most extensive mitogenomic sampling, our various resulting trees showed generally congruent topologies among pyraloid subfamilies, which are almost in accordance with previous multilocus studies, indicating the suitability of mitogenomes in inferring high-level relationships of Pyraloidea. However, nodes linking subfamilies in the “non-PS clade” were not completely resolved in terms of unstable topologies or low supports, and future investigations are needed with increased taxon sampling and molecular data. Unexpectedly, Orybina Snellen, represented in a molecular phylogenetic investigation for the first time, was robustly placed as basal to the remaining Pyralidae taxa across our analyses, rather than nested in Pyralinae of Pyralidae as morphologically defined. This novel finding highlights the need to reevaluate Orybina monophyly and its phylogenetic position by incorporating additional molecular and morphological evidence.